(untitled) (Nepalese Journal of Cancer, 2026)
Background: Myasthenia gravis (MG) is an autoimmune neuromuscular disorder characterized by fluctuating skeletal muscle weakness caused by antibodies against components of the neuromuscular junction, most commonly the acetylcholine receptor (AChR). Thymectomy is an established treatment for patients with MG, particularly those with AChR antibodies. Recently, uniportal subxiphoid has become the approach of choice offering improved postoperative recovery and reduced complications. Non-intubated thoracic surgery has also gained attention for minimizing anesthetic-related complications in MG patients. Case: Twenty two year old female diagnosed with AChR-positive, muscle specific tyrosine kinase (MuSK) negative MG receiving pyridostigmine who underwent uniportal subxiphoid VATS (Video assisted thoracoscopic surgery) thymectomy using local anesthesia and laryngeal mask airway (LMA) without muscle relaxant at B.P. Koirala Memorial Cancer Hospital (BPKMCH), Nepal. Preoperative evaluation included neurological assessment, serological testing, and radiologic imaging. The procedure was successfully completed without conversion to open surgery or endotracheal intubation. Postoperatively, the patient experienced an uneventful recovery and at 6 months follow up she was symptom free with reduced dose of pyridostigmine. Conclusion: Non-intubated uniportal subxiphoid VATS thymectomy is a safe and effective surgical option for MG patients. This technique may reduce postoperative complications and facilitate faster recovery compared with conventional intubated approaches. Our case highlights the potential benefits of minimally invasive thymectomy combined with non-intubated anesthesia in the management of myasthenia gravis.